On-Lay Versus Sub-Lay Mesh Repair for Ventral Hernia: A Retrospective Cohort Study - Syeda Areesha Shakeel; Osheen Abbasi; Ghulam Murtaza (Journal of Liaquat National Hospital)
Background: The most feared complication of hernia surgery is recurrence. There is no standard technique by which recurrence can be avoided. Objective: This study was conducted to test the hypothesis of whether the outcomes of sub-lay mesh are better than on-lay mesh repair for ventral hernias. Methods: This retrospective cohort study was conducted on patients who underwent open ventral hernia repair from 1st June 2016 - 31st April 2021. The primary outcome was recurrence and secondary outcomes were operative time, Surgical Site Infection (SSI) within 30 days, and seroma. Results: A total of 187 patients underwent ventral hernia repair and 69 were included in the study i.e. 35 in the sub-lay and 34 in the on-lay group. Both the groups were comparable for the baseline variables i.e. age, gender distribution, BMI, type of hernia, and content, with mean ± standard deviation age of 48.89 years ± 15.32 in the sub-lay and 52.7 ±12.3 in the on-lay group; however, the on-lay mesh was observed to be a preferred approach in patients with obesity or small defect <5 cms. No statistically significant difference was observed between sub-lay and on-lay groups for recurrence (2.9% vs. 5.7%, p-value 0.51), SSI (8.6% vs. 2.9%, p-value: 0.31), Mesh infection (2.9% vs. 2.9% p-value: 0.74), duration of surgery (median: 120 vs. 121 minutes, p-value 0.36) and seroma formation (2.9% vs. 2.9%, p-value 0.74), respectively. Conclusion: This study demonstrates no significant differences between sub-lay vs. on-lay mesh placement in terms of recurrence, seroma formation, and operative time; however, with the slightly higher (statistically insignificant) frequency of SSI in the sub-lay group.